Edible fungi for local and sustainable development in the Patagonian Andes forests of Argentina: A review - Barroetaveña, Carolina (2022)
Wild fungi are one of the most characteristic and diverse non-wood forest products from native and planted forest environments and grasslands in the Patagonian Andes. Through the technological and scientific platform “Patagonia Fungi, trails and tastes®”, we work to promote mycotourism and mycogastronomy as sustainable identity and inclusive economic and educational activities that promote local development, taking advantage of the outstanding regional tourist profile. We also work on the development of functional foods and promote the cultivation of edible and medicinal fungi. The main ob-jectives of this research were to define novel edible species and evaluate them for sustainable uses, including: environmental characterizations of their fruiting niches and ‘mycosilvicultural’ managements to increase their productivity; documentation and analysis of the ancestral uses and their processes of change; determination of the nutritional and nutraceutical profiles; studies of molecular genetic diversity of various genera; protocols for the domestication of wild species; evaluation and se-lection of lignocellulosic substrates for cultivation from available residues in Patagonian Andes; economic aspects related to the marketing and use in local gastronomy; evaluation of postharvest preservation techniques. Most relevant actions include the design and implementation of mycotourism trails, the promotion of an identity mycogastronomy; the inter-institutional management of protocols for sustainable harvesting and food safety practices; the incorporation of 21 new species in the Argentinean Food Code. We also work for food sovereignty through a spawn production laboratory fostering edible and medicinal fungi cultivation through courses and assistance to producers from family to productive scales.